2015
DOI: 10.1111/asj.12531
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations at LEPR gene locus associated with gene expression and phenotypic traits in Chinese cattle

Abstract: Current evidences show that copy number variations (CNVs) are linked to complex phenotypic traits. Leptin receptor (LEPR) gene plays a critical role in energy homeostasis and fat development and re-sequencing of the cattle genome revealed the CNV region (herein referred to as "I3 DNA") within the LEPR intron 3. In the present study, we qualified copy numbers of I3 DNA within LEPR gene in four cattle breeds (Qinchuan, Nanyang, Jinnan and Xianan) by quantitative PCR, and explored their impacts on LEPR gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…We found that the PIGY gene in sheep contains a copy number variation region located in exon 2, and it overlaps with 28 QTLs, including carcass weight and muscle density. Previous studies have reported that, in chickens, some QTLs associated with CNV fragments are related to body weight, carcass weight, and pectoral muscle mass [32,33]. Therefore, we focused on the PIGY gene to investigate the association between copy number variation and sheep economic traits.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the PIGY gene in sheep contains a copy number variation region located in exon 2, and it overlaps with 28 QTLs, including carcass weight and muscle density. Previous studies have reported that, in chickens, some QTLs associated with CNV fragments are related to body weight, carcass weight, and pectoral muscle mass [32,33]. Therefore, we focused on the PIGY gene to investigate the association between copy number variation and sheep economic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Third, quantitative PCR (qPCR) was performed to meansure CNVs [28]. Briefly, two pairs of quantitative primer were designed based on TGFβ3 (Gene ID: 396438, NC_006092.3) and PCCA gene sequences (Gene ID: 418774, NC_006088.3).…”
Section: Methodsmentioning
confidence: 99%
“…With the development of genomics, copy number variation has recently been shown to be associated with disease and phenotypic variation (Bujakowska et al, 2017;Keel et al, 2017;Shi et al, 2016). And it had been continuously confirmed to be able to influence individual phenotypic traits through gene dosage or structural variation (Bickhart et al, 2012;Wright et al, 2009).…”
Section: Discussionmentioning
confidence: 99%